Examining the diet quality of Canadian adults and the alignment of Canadian front-of-pack labelling regulations with other front-of-pack labelling systems and dietary guidelines - Lee, Jennifer J.; Ahmed, Mavra; Julia, Chantal; Ng, Alena Praneet; Paper, Laura; Lou, Wendy Y.; L’Abbé, Mary R. (Frontiers in Public Health, 2023)
Canada promulgated mandatory front-of-pack labelling (FOPL) regulations in 2022, requiring pre-packaged foods meeting and/or exceeding recommended thresholds for nutrients-of-concern (i.e., saturated fat, sodium, sugars) to display a ‘high-in’ nutrition symbol. However, there is limited evidence on how Canadian FOPL (CAN-FOPL) regulations compare to other FOPL systems and dietary guidelines. Therefore, the objectives of the study were to examine the diet quality of Canadians using the CAN-FOPL dietary index system and its alignment with other FOPL systems and dietary guidelines. Nationally representative dietary data from the 2015 Canadian Community Health Survey-Nutrition survey (n=13,495) was assigned dietary index scores that underpin CAN-FOPL, Diabetes Canada Clinical Practice (DCCP) Guidelines, Nutri-score, Dietary Approaches to Stop Hypertension (DASH) and Canada’s Food Guide (Healthy Eating Food Index-2019 [HEFI-2019]). Diet quality was examined by assessing linear trends of nutrient intakes across quintile groups of CAN-FOPL dietary index scores. The alignment of CAN-FOPL dietary index system compared with other dietary index systems, with HEFI as the reference standard, was examined using Pearson’s correlations and к statistics. The mean [95% CI] dietary index scores (range: 0-100) for CAN-FOPL, DCCP, Nutri-score, DASH, and HEFI-2019 were 73.0 [72.8, 73.2], 64.2 [64.0, 64.3], 54.9 [54.7, 55.1], 51.7 [51.4, 51.9], and 54.3 [54.1, 54.6], respectively. Moving from the ‘least healthy’ to the ‘most healthy’ quintile in the CAN-FOPL dietary index system, intakes of protein, fiber, vitamin A, vitamin C, and potassium increased, while intakes of energy, saturated fat, total and free sugars, and sodium decreased. CAN-FOPL showed moderate association with DCCP (r=0.545, p<0.001), Nutri-score (r=0.444, p<0.001), and HEFI-2019 (r=0.401, p<0.001), but poor association with DASH (r=0.242, p<0.001). Slight to fair agreement was seen between quintile combinations of CAN-FOPL and all dietary index scores (к=0.05-0.38). Our findings show that CAN-FOPL rates the dietary quality of Canadian adults to be healthier than other systems. The disagreement between CAN-FOPL with other systems suggest a need to provide additional guidance to help Canadians select and consume ‘healthier’ options among foods that would not display a front-of-pack nutrition symbol.